The impact of macroeconomic variables on the Johannesburg Stock Exchange (JSE) indices - Ndlovu, Nkosilathi (Department of Finance and Tax, 2023)
This study aims to examine the long-term relationship between macroeconomic factors and stock market index levels for selected indices through a structural model which consists of a security valuation approach in the form of Dividend Discount Model(DDM) and an Engle and Granger cointegration model. The macroeconomic variables examined include inflation, money supply, exchange rates, index earnings, and interest rates. The data was gathered from various sources such as Bloomberg, and I-Net and was analysed over a period of 20 years from 2001 to 2021 on a monthly basis. Engle and Granger cointegration and the Error Correction Model (ECM) have been used to examine the long-term relationship and the deviation from long-run market equilibrium. In addition, this study also applies the impulse response function and variance decomposition to evaluate the stock market's response to macroeconomic shocks and to determine the magnitude of influence of each variable on the share price level. The results reveal that macroeconomic variables and stock market index levels are cointegrated and index levels deviate from long-term market equilibrium. Future research may consider evaluating qualitative variables and share price long-term relationship, this might answer the question of investor sentiments impact on mean reversion. Key words: Engle and Granger Cointegration, Error Correction Model, Index levels, Macroeconomic Variables